Localization of fluorescent gold nanoparticles throughout the eye after topical administration - Raîche-Marcoux, Gabrielle; Méthot, Sébastien; Tchatchouang, Ange; Bettoli, Camille; Maranda, Cloé; Loiseau, Alexis; Proulx, Stéphanie; Rochette, Patrick J.; Genin, Emilie; Boisselier, Élodie (Frontiers in Medicine, 2025)
The human eye is a highly intricate sensory organ. When a condition requiring treatment occurs, eyedrops, which represent 90% of all ophthalmic treatments, are most frequently used. However, eyedrops are associated with low bioavailability, with less than 0.02% of therapeutic molecules reaching the anterior chamber. Thus, new delivery systems are required to ensure sufficient drug concentration over time at the target site. Gold nanoparticles are a promising avenue for drug delivery; however, they can be difficult to track in biological systems. Fluorescent gold nanoparticles, which have the same ultrastability and biocompatibility as their nonfluorescent counterpart, could act as an effective imaging tool to study their localization throughout the eye after administration. Thus, this study (1) synthesized and characterized fluorescent gold nanoparticles, (2) validated similar properties between nonfluorescent and fluorescent gold nanoparticles, and (3) determined their localization in the eye after topical application on ex vivo rabbit eyes. The fluorescent gold nanoparticles were synthesized, characterized, and identified in the cornea, iris, lens, and posterior segment of rabbit eyeballs, demonstrating tremendous potential for future drug delivery research.